Efforts to Resolve Conflicts Between Villagers in a Restorative Manner: The Role of Bhabinkamtibmas as Mediators in the Perspective of National and Local Law - Ari Mistari; Harmono Harmono (Jurnal Legisci, 2026)
Background. Conflicts between villagers are a recurring phenomenon and cannot always be resolved effectively through formal legal mechanisms. In practice, conflict resolution is more often carried out through social-relationship-based approaches, such as deliberation and mediation involving village officials and communities. Aims. This study aims to examine how conflict resolution among villagers is carried out through a restorative approach, how the role of Bhabinkamtibmas as a mediator is practiced, and how the practice is viewed from the perspective of national and local law. Methods. This research uses a socio-legal approach and a qualitative method, combining normative analysis of laws and regulations with empirical findings in the field. Data were obtained through interviews with Bhabinkamtibmas and village officials, as well as a review of relevant literature and regulations. The analysis was carried out by relating conflict resolution practices to the theoretical framework of restorative justice and the legal construction that governs it. Result. The results of the study show that conflict resolution between villagers through a restorative approach has basically been underway, but does not always reflect the principle of restoring relationships in its entirety. The role of Bhabinkamtibmas is evolving into that of a mediator operating in the social space, but it has not yet been fully supported by a clear legal framework. In practice, conflict resolution is often more of a social compromise shaped by power relations than the result of an ideal restorative process. Conclusion. This research offers a new perspective by positioning restorative justice not merely as a normative concept but as a social practice operating at the intersection of formal law, local norms, and power dynamics in society. Implementation. These findings suggest that the effectiveness of conflict resolution is determined not only by the existence of rules but also by the system's ability to accommodate complex social realities.